The adequacy of the Tanzanian law on e-commerce and e-contracting : possible solutions to be found in international models and South African legislation - Nangela, Deo John (Department of Commercial Law, 2015)
This dissertation examines Tanzania’s legal framework in the light of the modern information and communication technologies, especially the Internet and e-commerce. The main goal is to assess the adequacy of the existing law and to provide recommendations for reforms that will reflect the borderless nature of e-contracts. These reforms must ensure the certainty and predictability needed for successful cross-border commerce. Achievement of these aims will build confidence and trust on the part of business entities and consumers, and, in addition, will enhance free trade, strengthen the growing market-based economy, and integrate Tanzania into the global economy.